Benefits of DPP-4 Inhibitors in Patients with Type 2 Diabetes and Cardiovascular Risk - Vinall, Maria (MD Conference Express, 2013)
Many studies have shown that improved glucose control in patients with diabetes reduces microvascular complications. Dipeptidyl peptidase-4 (DPP-4) inhibitors improve glucose control and were thought to reduce the risk of cardiovascular events and all-cause mortality in patients with type 2 diabetes [Monami M et al. Diabetes Obes Metab 2013]. This article discusses the Examination of Cardiovascular Outcomes With Alogliptin Versus Standard of Care trial [EXAMINE; NCT00968708] and Saxagliptin Assessment of Vascular Outcomes Recorded in patients with diabetes mellitus [SAVOR]-TIMI 53 trial [NCT01107886] trials.